Selective UV-filter detection with sensors based on stainless steel electrodes modified with polyaniline doped with metal tetrasulfonated phthalocyanine films - Moreira, Luiz Fernando; de Vasconcelos Lanza, Marcos Roberto; Tanaka, Auro Atsushi; Taboada Sotomayor, Maria Del Pilar [UNESP] (Royal Soc Chemistry, 2009)
This work describes the construction and application of two amperometric sensors for sensitive UV-filter determination. The sensors were prepared using stainless steel electrodes in which polyaniline (PANI) was electrochemically polymerized in the presence of nickel (NiPcTS) or iron (FePcTS) tetrasulfonated phthalocyanines. The sensor surface characterizations were carried out using atomic force microscopy (AFM). The PANI/NiPcTS sensor was selective for the chemical UV-filter p-aminobenzoic acid (PABA) and the PANI/FePcTS sensor was selective for octyldimethyl-PABA (ODP), both in a mixture of tetrahydrofuran (THF) and 0.1 mol L(-1) H(2)SO(4) at a volume ratio of 30 : 70, and with an applied potential of 0.0 mV vs. Ag vertical bar AgCl. A detailed investigation of the selectivity was carried out for both sensors, in order to determine their responses for ten different UV filters. Finally, each sensor was successfully applied to PABA or ODP quantification in sunscreen formulations and water from swimming pools.